Kendala Perolehan Tanah Untuk Kegiatan Usaha Perseroan (Studi Kasus di Kabupaten Klaten) - Partha, Grace Cesar Asvini; Aidi, Zil (Program Studi Magister Kenotariatan, Fakultas Hukum, Universitas Diponegoro, 2024)
ABSTRACTThe company understands the importance of land acquisition for the smooth operation of its business activities. However, in practical fieldwork, the company encounters several obstacles in acquiring land. The purpose of writing this journal article is to identify obstacles and efforts to resolve land rights acquisition issues for the company's operations in Klaten Regency. The research method employed is empirical juridical, focusing on the implementation of normative legal provisions in societal legal events. Research findings indicate that obstacles in land rights acquisition can be overcome through dedicated land acquisition for industrial zones. The primary challenge in acquiring land for the company's business activities is the extended process of obtaining Building Use Rights on behalf of the company and significant land price escalation.Keywords: Company; Business Activity; Land Bank.ABSTRAKPerusahaan (perseroan) memahami pentingnya perolehan tanah untuk kelancaran kegiatan usahanya. Namun, dalam praktek lapangan, perusahaan menghadapi sejumlah kendala dalam mengakuisisi tanah. Top of Form Tujuan dari penulisan artikel jurnal ini adalah untuk mengetahui kendala dan upaya menyelesaikan masalah perolehan hak atas tanah untuk kegiatan usaha perseroan di Kabupaten Klaten. Metode penelitian yang digunakan adalah yuridis empiris, yang berfokus pada implementasi ketentuan hukum normatif dalam peristiwa hukum masyarakat. Hasil penelitian menunjukkan bahwa kendala dalam perolehan hak atas tanah dapat diatasi dengan pengadaan tanah khusus untuk kawasan industri. Kendala utama dalam perolehan tanah untuk kegiatan usaha perseroan adalah lamanya proses perolehan Hak Guna Bangunan atas nama perseroan dan kenaikan harga tanah yang signifikan.Kata Kunci: Perseroan; Kegiatan Usaha; Bank Tanah